Credit Constraints, Heterogeneous Firms and Loan Defaults - Jarko Fidrmuc; Pavel Ciaian; d'Artis Kancs; Jan Pokrivcak (Economics and Econometrics Research Institute (EERI), 2011)
In light of the recent financial and economic crisis the present paper analyzes the determinants of loan default. We employ a unique firm-level panel data of 700 bank loans given to small and medium sized enterprises in Slovakia between 2000 and 2005 to investigate three loan default hypothesis. Testing the Sector-Risk Hypothesis, we find that agro-food industry does not exhibit higher default rate than other sectors. Testing the Firm-Risk Hypothesis, we find that highly indebted firms are more likely to default on their loan than other firms. Testing the EU Subsidy Hypothesis we find that the newly introduced subsidy system, which is decoupled from production, provides a secure source of income and hence reduces the probability of loan default.
Keywords: G33; G21; C25; Q14; 330; Bank credit; loan default; credit constraints; heterogeneous firms